SARI TEMULAWAK (Curcuma XanthorhizzaRoxb) PADA VOLUME ASI IBU POSTPARTUM) - Indah Putri Ramadhanti; Maili Yusra; Fontanella Fontanella (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Based on 2017 WHO data, exclusive breastfeeding reached 43.5%, far from meeting the world target of 95%. In Indonesia, it only reached 61.3% of the 80% target. The main factor is due to the low production of breast milk at the beginning of breastfeeding and the lack of knowledge of the mother. Efforts to overcome the problem are to stimulate milk production by giving ginger extract which is rich in lactogogu, polyphenols, and flavonoids to stimulate the hypothalamus to maximize the production of the hormone prolactin compared to other herbs. The purpose of this study was to determine the effect of giving ginger extract (Curcuma xanthorhizzaRoxb) on the volume of breast milk of postpartum mothers in the Airpura Health Center Work Area in 2020. This type of pre-experimental research with a one-group pretest and posttest research design. The population was all primiparous postpartum mothers on the 4th to 7th day as many as 35 people, the sample using purposive sampling technique was 14 people. The instrument is an observation sheet. The data were normally distributed using a paired sample t-test. The univariate analysis showed that volume of pretest breast milk was 21.07 cc ± SD 7.385, the post-test breast was 50.71 cc ± 11.906. The results of the analytic bivariate showed that ginger extract was given with p-value=0.001 (p<0.05). The conclusion is that temulawak extract affects increasing the volume of postpartum mother's milk. It is suggested that ginger extract helps the success of exclusive breastfeeding